1998
DOI: 10.1108/13639519810228741
|View full text |Cite
|
Sign up to set email alerts
|

Victim‐precipitated homicide: police use of deadly force in British Columbia

Abstract: This study examines the underlying reasons for the police use of deadly force and potential deadly force, in the Province of British Columbia, Canada, during the period 1980‐94. Within this context, interactional violence and the phenomenon of victim‐precipitated homicide are examined in relation to the police use of deadly force. This study analyzes 58 separate documented incidents in which municipal and Royal Canadian Mounted Police officers, within the Province of British Columbia, have been confronted by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 7 publications
1
34
0
Order By: Relevance
“…Unique to SbC subjects is the use of an "outrageous act" such as committing a violent crime that triggers law enforcement involvement in the SbC incident (Drylie, 2006;Lord, 2004;Mohandie & Meloy, 2000). The verbalization of the subject's desire to die by forcing police officers to shoot and/or life threatening behavior toward police or other citizens (that comes to the attention of the police) also appears to be unique to SbC subjects (Hutson et al, 1998;Lord, 2001;Parent & Verdun-Jones;). In addition, prevalent among SbC subjects is their general attachment with other people.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…Unique to SbC subjects is the use of an "outrageous act" such as committing a violent crime that triggers law enforcement involvement in the SbC incident (Drylie, 2006;Lord, 2004;Mohandie & Meloy, 2000). The verbalization of the subject's desire to die by forcing police officers to shoot and/or life threatening behavior toward police or other citizens (that comes to the attention of the police) also appears to be unique to SbC subjects (Hutson et al, 1998;Lord, 2001;Parent & Verdun-Jones;). In addition, prevalent among SbC subjects is their general attachment with other people.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Researchers (Drylie, 2006;Homant & Kennedy, 2000;Lord, 2000Lord, , 2004Parent & Verdun-Jones, 1998) have concluded that there are a number of individual and situational factors that are unique to SbC subjects, as well as factors that are shared with other suicidal victims. Criminal history and a criminal act preceding (and often precipitating) the lethal act are prevalent among SbC subjects.…”
Section: Literature Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Other research indirectly suggests that African American youth may view suicide as more stigmatizing in that African American youth are more likely to deny suicide intent, even after making a suicide attempt (Summerville et al 1992;Forbes et al 1999). Research suggests they may also engage in ''disguised'' suicidal behaviors in the form of ''victim-precipitated homicides'' in which the victim intentionally engages in behavior in a life-threatening context that almost guarantees that another person (e.g., police officer) will kill the victim (Parent 1999). Information was obtained from focus groups because this methodology particularly lends itself to exploring specific aspects of the social and attitudinal contexts of the church and allows us to explore those aspects of the church context that may either support or hinder help-seeking behaviors in adolescents.…”
Section: Introductionmentioning
confidence: 98%
“…Others have wondered whether African American suicides may be "disguised" in the form of "victim-precipitated homicides" (Garrison, Addy, Jackson, McKeown, & Waller, 1991). Victim-precipitated homicide is viewed essentially as an act of suicide because the victim intentionally engages in behavior in a life-threatening context that almost guarantees that another person (e.g., police officer) will kill the victim (Parent, 1999;Wolfgang, 1958). Although it has been estimated that nearly 30% of urban homicides are victim-precipitated (Van Zandt, 1993), it is not formally recognized as a form of suicide.…”
mentioning
confidence: 99%